Avaliação da prevalência de anomalias dentárias associadas à agenesia de incisivos laterais superiores - Alencar, Bárbara Maria de (2009)
The aim of this study consisted in evaluating, in patients with agenesis of maxillary lateral incisors, the prevalence of other dental anomalies, i.e, position, number and size, as well as comparing these prevalences with those expected for the general population. In order to perform this comparison, a composed sample was selected, including orthodontic records of 170 patients, 6 to 47 years old, presenting agenesis of, at least, one maxillary lateral incisor. The studying material included periapical x-rays, panoramic x-rays, cast models and clinic files of the patients. Through the examination of this material, the following information was recorded: age and ethnicity of the patients; the history of extraction of permanent teeth; presence of other dental associated anomalies, including agenesis of permanent teeth, ectopies, infra-occlusion of the second deciduous molars, peg-shaped permanent maxillary lateral incisors and supernumerary teeth. These pieces of information were compared with the prevalence expected for the general population by the application of the Qui-square test (²). Additionally, the Odds ratio was calculated and the results were considered at the level of significance of 5%. A strong association between agenesis of maxillary permanent lateral incisors and other permanent teeth agenesis, as well as microdontia of maxillary lateral incisors and some important anomalies of position was verified. The results are consistent with the hypothesis that dental agenesis, microdontia and some ectopies are biological co-variables in a complex of genetically associated dental anomalies.